Bobos in paradise: Urban politics and the new economy - Gilles Saint-Paul (Kiel Institute for the World Economy (IfW), 2017)
This paper provides some elements to explain the observed takeover in some urban areas of a new kind of elite associated with new economy jobs, also known as "bourgeois boheme" (bobos). This takeover has been associated with greater investment in urban amenities and "clean" means of transport, with adverse effects on commuting time. The model allows us to explain those developments by productivity growth in the new economy, and by the differences in production processes between the new and old economies. The consequences of bobo takeover for house prices and employment of unskilled service workers are also discussed. A bunkerized equilibrium in which skilled workers in the old economy no longer reside in the city and have been replaced by service workers is studied. In such an equilibrium urban amenities are at their maximum and commuting flows have been eliminated. For some parameter values, bobos are better-off under bunkerization, in which case they may gain by favoring it with a "diversity" subsidy for unskilled workers to reside in the city.
Keywords: H7; R3; R4; R5; 330; new economy; urban amenities; bobos; residential choice; local public goods; urban voting models; bunkerization